Adipofascial anterolateral thigh free flap for hemifacial atrophy - Agostini, T (Pacini Editore SpA, 2009)
Restoration of a harmonious and pleasant appearance is a crucial aspect of surgical treatment for many congenital and acquired deformities of the face. A 38-year-old female patient with residual scarring on the right hemiface following evacuation of a odontogenic phlegmon underwent microsurgical reconstruction with a free adipofascial anterolateral thigh free flap. A stable result was achieved 7 years later. Thanks to adipofascial anterolateral thigh free flap fixation onto the periosteum a very good long-lasting aesthetic and dynamic result was obtained; this approach can be used in patients both with severe and mild abnormalities. Whereas many methods of facial contour restoration are described in the literature, in Authors’ opinion, microsurgical techniques are the gold standard unless contraindications; fasciocutaneous flaps, in particular, have shown the best aesthetic results since they can be sculptured to match the defect and stable anchoring is possible thanks to the thick fascia of the anterolateral thigh free flap.